Hubungan Antara Kebersyukuran dengan Kebahagiaan pada Guru Honorer - M. Khairullah; Nina Zulida Situmorang; Ahmad Muhammad Diponegoro (Psyche 165 Journal, 2021)
This reseach aims to determine the relationship between thanksgiving and happiness in honorary teachers. The research method is a quantitative method. The data collection techniques used scale of gratitude and scale of happiness. The subjects of this research were 105 teachers of the State Elementary School in Masbagik sub-district, East Lombok district. The analysis technique used is Product Moment Correation analysis by using SPSS 23.00 For Windows. The result of data analysis showed that the coefficient of correlation was R = 0.690 with a significance level of 0.000 (p <0.01). This research indicated that the contribution which is given by gratitude to happiness is 47,6 %, it means the relationship between the variables of gratitude and happiness for honorary is very significant.